ADJUSTMENT FACTORS FOR INTERNATIONAL STUDENTS IN UNITED STATES UNIVERSITIES - Yeh, Chia Jung; Singh, Ajay; Shaughnessy, Michael; Chung, Chih-hung; Ratto, Dominique (Acta Scientiae et Intellectus, 2024)
The purpose of this research study is to identify factors that influence the adjustment and academic achievement of East Asian students in United States Universities. Adjustment challenges are primarily attributable to English language proficiency, and culture. Achievement is impacted by English language proficiency, cultural and educational background. A qualitative research design was utilized for this research study. Successful support interventions are reviewed and implications for practice are discussed for East Asian students in the United States.